Comparative performance and health economic analysis of prenatal screening for down syndrome in Fujian province, China - Lin Zheng; Nuolan Yin; Meiying Wang; Hailong Huang; Shuyu Zhang; Linjuan Su; Liangpu Xu (Scientific Reports)
Abstract To compare the performance of first-trimester serum screening (FTSS) and non-invasive prenatal testing (NIPT) in detecting fetal chromosomal aneuploidies trisomy 21 (T21) and trisomy 18 (T18), and to evaluate the cost-effectiveness and clinical feasibility of four screening strategies for the prevention of Down syndrome (DS) from a health economics perspective. This retrospective study included 33,559 pregnant women who underwent DS screening at Fujian Maternity and Child Health Hospital between February 25, 2022, and December 29, 2023. Participants were divided into an FTSS group (n = 23,136) and an NIPT group (n = 10,423) based on the type of screening received. All subjects were followed for eight months postpartum to collect pregnancy outcome data. Screening performance was compared between the two groups based on prenatal diagnostic results. Subsequently, four screening strategies were constructed and assessed using cost-effectiveness analysis and NIPT price sensitivity analysis to determine their health-economic value. A comparison of screening performance between the two groups showed that NIPT had significantly higher specificity (99.96%) and positive predictive value (55.56%) than FTSS (specificity: 92.93%, positive predictive value: 0.91%). Meanwhile, the false-positive rate of NIPT (0.04%) was notably lower than that of FTSS (7.07%). Cost-effectiveness analysis of the four strategies indicated that strategy 2 was the most cost-effective, with a cost-effectiveness ratio (CER) of 1,252,400 CNY and an incremental cost-effectiveness ratio (ICER) of -3,626,700 CNY, achieving improved screening outcomes while reducing costs. Sensitivity analysis further demonstrated that even when the screening scale expanded under strategy 4 or when NIPT prices fluctuated between 700 and 2,100 CNY, strategy 2 maintained the lowest CER. NIPT is superior to FTSS in terms of screening efficacy. Based on a health economic evaluation, among the four strategies, Strategy 2 (using NIPT as conditional screening) offers the best cost-effectiveness while improving detection efficacy, making it the optimal strategy recommended in this study.